Leveraging breed-specific data to guide targeted greenhouse gas mitigation strategies in Uganda's dairy sector - Mwema, Emmanuel; Isiaho, Glarion; Adhiambo, Sarah; Rubayiza, Isaac; Gonzalez Quintero, Ricardo; Agasi, Herbert; Ouma, Emily; Notenbaert, An (2025)
Dairy production plays a vital role in Uganda, supporting 6.8 million households and contributing 17% to the country's total agricultural gross domestic product. Despite its potential, dairy production in the region face numerous challenges, including low productivity, soil infertility, climate risks and limited resources, particularly land, in the smallholder farming systems. Furthermore, dairy production practices are under scrutiny due to their increasing carbon footprint, which not only impacts the sector but also contributes to frequent instances of climate variability. To evaluate the extent of these issues and propose priority dairy interventions, we conducted a case study in the Mpigi and Nakasongola districts, two key cattle corridors in the central region. This study aimed at evaluating the impact of the current dairy production practices on breed-specific greenhouse gas emissions (GHGe) and the likely changes due to the adoption of the bundled dairy husbandry interventions (animal health, genetics, feeds and forages) proposed by the research partners in the study sites. Using I-CLEANED, an ex-ante environmental footprint calculator for livestock systems, we evaluated the traditional (Ankole and Nganda) and exotic breeds (Friesian, Ayrshire, Guernsey, Jersey) in seven villages across the study sites. Data for parameterization were obtained from the AADGG genetic gains platform, including information on breeds, milk production, weight, lactation periods, and feed baskets from 1,500 dairy farmers across two districts. This was further complemented by data from the Gendered Feed Assessment Survey of 2023, which focused on crop production, livestock, and feed resource availability. Additionally, information on feed nutritive values, agroclimatic conditions, and weight gains was gathered from secondary sources. To validate the data on feed intake, milk production, and crop inputs, follow-up interviews were conducted with farmers. The selection of breeds and villages in this study was based on the prevalence of breeds across multiple villages and the completeness of data obtained after a rigorous validation process. Baseline GHGe intensity ranged from 1.09 to 2.74 kg CO₂ eq. kg⁻¹ FPCM in Mpigi and 1.30 to 2.15 kg CO₂ eq. kg⁻¹ FPCM in Nakasongola. Under the intervention scenario, emissions declined to 0.79–2.15 and 1.01–1.81 kg CO₂ eq. kg⁻¹ FPCM, respectively. Greater reductions were observed in Mpigi, with average declines of 0.3–1.0 kg CO₂ eq. kg⁻¹ FPCM, indicating stronger mitigation effects of the bundled interventions. Overall, local breeds exhibited slightly higher emission intensities than exotic breeds, with Jersey showing the best GHG efficiency among the exotics. Feed quality and availability, animal productivity and reproductive performance influenced emission levels. In Nakasongola, reducing natural pasture intake, improving animal health, and gradually integrating improved breeds could lower emissions and enhance milk supply. In Mpigi, improving feed conversion efficiency and reproductive performance among exotic breeds offers immediate mitigation gains.